THE FRACTIONAL METRIC DIMENSION OF GRAPH COMB PRODUCT - JUMEIDIL ANALYES PERDANA (NIM.10108006); Pembimbing : Dr. Suhadi Wido Saputro , M.
Let be a connected graph of order. A vertex resolves a pair of vertices of if the distance from u to x in is not equal to the distance from v to x in. For A pair of vertices of, a resolving set of of is a vertex set. A function is called as resolving function of, if for every distinct vertices of. The fractional metric dimension of is defined as minimal resolving function whrere. A comb product graphs between two connected graph and , denoted by, is a graph obtained by taking 1 copy of graph and copies of graph by grafting the-i-th copy at the vertex to the-i-th vertex of. We determine the fractional metric dimension of, where a connected graph of order at least 2 and is either complete graph with, or star graph with, or cycle graph with, or with.